Bioelectrical impedance and indicators of body fat and cardiovascular risk in adolescents - Ismael Forte Freitas Júnior; Rômulo Araújo Fernandes; Camila Buonani; Clara Suemi da Costa Rosa; Denise Rodrigues Bueno; Aline Francielle Motta Segatto; Arli Ramos de Oliveira (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n1p19 The purpose of this study was to analyze the relationship between bioelectric impedance and adiposity and elevated cardiovascular risk indicators, and its effectiveness for detecting appropriate nutritional status, according to the Body Mass Index. A Cross-sectional study. The sample included 900 subjects, both males and females, with ages ranging from 11 to 17 years. Nutritional status was determined according to both Body Mass Index and relative body fat, estimated by bioelectric impedance. For both sexes, bioelectric impedance was signifi cantly correlated (p< 0.05) with all adiposity and cardiovascular risk indicators. Furthermore, it exhibited high specifi city for indicating nutritional status. It can be concluded that bioelectric impedance is a useful tool for body composition assessment. It can also be concluded that in young populations, care musty be taken when choosing equations to estimate relative body fat.